CAPITAL ADEQUACY, LIQUIDITY CREATION, AND PANDEMIC CRISES: AN EMPIRICAL STUDY ON INDONESIAN RURAL BANKS - Al Hashfi, Rizqi Umar (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2022)
The aim of this article is to examine the relationship between capital adequacy, liquidity creation, and the pandemic crisis in Rural Banks. There are 435 banks as samples from 2019 – 2021. For hypothesis testing, I use regression techniques within-estimator and two-stage least square to overcome heterogeneity and endogeneity problems. The results support the theory of financial fragility crowding out so that capital adequacy is negatively associated with liquidity creation. In fact, the nexus is greater during the covid-19 pandemic crisis. In the end, this research has theoretical and practical implications.